Synthesis and Characterization of Pyrrolidinium-based Ionic Liquid as A New Biodegradable Oil Dispersant - Ahmad Shobri, Alya Nabilah (IRC, 2016)
Oil spills are one of the disasters that could happen in the oil and gas industry. Thus, the method of cleaning up these oil spills are important to maintain the stability of the environment. One of these methods include the dispersion of oil using dispersants. This is when the use of ionic liquid-based surfactants is necessary. In this work, Pyrrolidinium-based ionic liquids are synthesised and their characteristics are analysed. These ionic liquids are developed via metathesis. The results of the synthesised ionic liquids are confirmed qualitatively through the use of the H-NMR spectroscopy. This finding is further supported by the investigation of the surface tension properties of the ionic liquids-based surfactants.